2019
DOI: 10.1111/ctr.13651
|View full text |Cite
|
Sign up to set email alerts
|

Impact of induction immunosuppression on patient survival in heart transplant recipients treated with tacrolimus and mycophenolic acid in the current allocation era

Abstract: Background:The practice of induction therapy with either rabbit anti-thymocyte globulin (r-ATG) or interleukin-2 receptor antagonists (IL-2RA) is common among heart transplant recipients. However, its benefits in the setting of contemporary maintenance immunosuppression with tacrolimus/mycophenolic acid (TAC/MPA) are unknown. Methods:We compared post-transplant mortality among three induction therapy strategies (r-ATG vs IL2-RA vs no induction) in a retrospective cohort analysis of heart transplant recipients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“… 7 , 11 Moreover, reports from 2018 and 2019 suggest increased mortality with the use of LDA induction with rATG. 12 , 13 Of interest will be the results of an ongoing pilot randomized study of LDA induction with rATG in heart transplantation (NCT03292861). 19 Thus, as of May 2020, conflicting data supporting its use and its high cost explain why LDA induction is not universally adopted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 , 11 Moreover, reports from 2018 and 2019 suggest increased mortality with the use of LDA induction with rATG. 12 , 13 Of interest will be the results of an ongoing pilot randomized study of LDA induction with rATG in heart transplantation (NCT03292861). 19 Thus, as of May 2020, conflicting data supporting its use and its high cost explain why LDA induction is not universally adopted.…”
Section: Discussionmentioning
confidence: 99%
“… 7 However, LDAs are not universally used because of conflicting reports of efficacy. 11 - 13 Further limiting their use is the concern for increased adverse effects related to infection. 6 , 7 , 13 Finally, older studies that reported benefits from LDA induction included antiquated immunosuppression regimens, raising the question of whether LDA induction is beneficial when combined with newer immunosuppressive agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gen- eral, only 46% of recipients receive induction therapy preoperatively, as it does not seem to affect survival post-HTx [100]. More acute rejection episodes were observed in recipients who received induction therapy using rabbit antithymocyte globulin (ATG) or IL2RA therapy (20.2% vs. 19%, respectively) compared to those who did not receive any induction (16.8%) prior to HTx [101]. Similar findings were also reported in the ISHLT registry report of 2019, with no difference in treated rejection episodes observed between recipients who received ATG as opposed to IL2RA therapy [3].…”
Section: Inductionmentioning
confidence: 99%
“…While the studies included in these meta-analyses have a high degree of bias, it is still important to consider the potential different efficacies of the available induction agents. Amin et al investigated the survival of 12,103 OHT recipients from 2006 to 2015 and reported an increase in mortality associated with induction therapy, without identifying any benefits in reductions rejection rates (20). Similarly, a retrospective analysis by Whitson et al (21) of 17,857 OHT recipients from 1987 to 2012 failed to show an overall survival benefit from induction therapy.…”
Section: Prior Studiesmentioning
confidence: 99%